Angara EU Delegation's dire warning is a gross misinterpretation (2017)
Statement of Edgardo J. Angara to the Inquirer banner story, "Int'l groups press probe of drug kills"
Keywords: Angara, Edgardo J. -- Speeches, addresses, etc; European Union -- Foreign relations; Duterte administration -- Foreign relations